Cytoreductive surgery with a hyperthermic intraperitoneal chemotherapy program: Safe after 40 cases, but only controlled after 140 cases. Issue 12 (December 2015) - Voron, T.; Eveno, C.; Jouvin, I.; Beaugerie, A.; Lo Dico, R.; Dagois, S.; Soyer, P.; Pocard, M.
Abstract: Background: Cytoreductive surgery (CRS) with hyperthermic intraperitoneal chemotherapy (HIPEC), used to treat peritoneal surface malignancies (PSM), is a complex procedure with significant major morbidity (MM). Objective: To investigate the learning curve (LC) of CRS with HIPEC in a new specialized surgical unit with a fully trained senior surgeon and individualize the variables associated with morbidity and oncological results. Methods: A total of 290 consecutive patients with PSM were included. Complete CRS with HIPEC was performed in 204 patients. A risk-adjusted sequential probability ratio test was used to assess the LC on the basis of rates of incomplete cytoreduction (IC) and MM. Results: Complete CRS, MM, and mortality rates were 70.4%, 30.4%, and 2.5%, respectively. Tumor histotype, a high peritoneal cancer index (PCI) and the invaded region were the major independent risk factors for IC, whereas previous surgery, high PCI, stomia realization and blood transfusion were predictors of MM. RA-SPRT showed that 140 and 40 cases were needed to achieve the lowest risk of IC and MM, respectively. Conclusion: CRS with HIPEC to treat PSM has a steep LC. Drastic selection has to be made at the beginning, excluding high PCI, rare peritoneal disease and patients previously operated on.